BERTEOLOGI KONTEKSTUAL DARI TANGGANG-TRANGBU (TRADISI RAMAH TANAH MASYARAKAT WANGSINA) - Eunike Molebila; Delila Tanaem (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
Land and the people who live on it have intimate interconnections. This is expressed in the form of local wisdom. Local wisdom itself has made many valuable contributions to land management by paying attention to aspects of sustainable ecosystems (sustainability). One of the local wisdoms is tranggang-trangbu in the Wangsina Community of Langkuru Village, Pureman District, Alor Regency. This local wisdom is based on the belief that even years are good years and odd years are bad years. Therefore, the Wangsina people will only plant in even years, while their agricultural land is rested on odd years. The location for the implementation of this tradition is on three large mountain slopes and will be cleared one by one (rotation system) every even year, so that the total time to rest the land that has been cultivated is 6 years. However, several problems arise in the implementation of this local wisdom, because this tradition is clashed with theological and economic understanding. These things, make the Wangsina people